Infantile Hemangioma Treated with Propranolol Readmission Trends, Complications of Therapy, and Cost: A PHIS Database Study. (9th September 2022) - Abu-Rmaileh, Muhammad; Hairston, Hayden C.; Zaniletti, Isabella; Kompelli, Anvesh; Davis, Kyle P.; Gardner, James Reed; Bolin, Elijah H.; Richter, Gresham T.
Abstract : Objective . To examine admission trends, complications, and costs for inpatient infantile hemangioma (IH) associated with propranolol therapy utilizing the Pediatric Health Information System (PHIS) database. Study Design . A retrospective cohort study was completed using the PHIS database. The PHIS database was queried from 2008 to 2020 for children without cardiac disease and between the ages of three weeks and one year who were admitted with a diagnosis of IH and administered propranolol. Admissions were trended annually and by geographic region. Primary outcomes were length of stay (LOS), readmission, mortality, propranolol-related complications, and costs. Bivariate and multivariable analyses were employed to identify predictors of the primary outcomes. Results. A total of 2290 unique patient encounters were identified. Admissions steadily decreased after 2011, with variations by geographic region. There was no mortality and only 60 (2.6%) propranolol-related complications. African-American race (odds ratio (OR) 1.20 [95% CI: 1.02-1.41]), respiratory comorbidities (OR 2.04 [95% CI: 1.42-2.93]), neurologic conditions (OR 1.34 [95% CI: 1.09-1.59]), admission to an intensive care unit (OR 1.31 [95% CI: 1.09-1.59]), bronchospasm (OR 1.37 [95% CI: 1.22-1.55]), and hyperkalemia (OR 1.86 [95% CI: 1.08-3.20]) were associated with increased LOS. Neurologic conditions (OR 2.87 [95% CI: 1.76-4.67]) and respiratory comorbidities (OR 2.48 [CI: 1.43-4.30]) were associated with readmission. Average cost per admission was 5, 158 (3, 259 to 8, 560 range). Conclusion . There is an overall national decline in rate of admissions for IH propranolol therapy. Inpatient admission may be beneficial for patients with neurologic or respiratory conditions.